APPLICATION OF LARVITRAP AND OVITRAP TO CONTROL Aedes sp. IN DHF ENDEMIC AREAS - Arif Widyanto; Aris Santjaka (Poltekkes Kemenkes Semarang, 2020)
Alternative mosquito vector control at this time that is cheap, practical and relatively safe to the environment is needed by developing countries such as Indonesia.One of the methods of controlling Aedes sp without insecticides is the use of larvae traps (larvitrap). The working principle of larvitrap is that the eggs trapped in the tool The incidence rate (IR) of Dengue Hemorrhagic Fever per 100.000 population in Central Java in the last five years is as follows: 2011 amounted to 15,27 in 2012 amounted to 19,29 in 2013 amounted to 45,52 in 2014 amounted to 32,95 and years 2015 amounted to 34,87. Since 2010 DHF has spread to all districts / cities in Central Java. Larvitrap and ovitrap are tools that can be used as traps for Aedes sp. Both of these tools can be used with additional attractants which can serve to attract the attention of Aedes sp. in order to lay eggs on the tool. Larvae that hatch from eggs in the larvitrap eventually cannot become adults and will die. Mosquito eggs trapped in the ovitrap can be destroyed so that they do not develop into adult mosquitoes. The research objective was to determine the effectiveness of using larvitrap and ovitrap as a control tool for Aedes sp (DHF vector).The research method used is experimental research. The research location is in the Banyumas Regency area. Larvitrap made of plastic jars and pralon was painted black and modified using gauze on the top. Ovitrap from plastic cups was painted black and given an ovistrip. Larvitrap and ovitrap were placed in DHF endemic areas. After the larvitrap and ovitrap are taken, the number of trapped Aedes sp and the larvitrap / ovitrap index is calculated. Furthermore, analyzed the effectiveness of using larvitrap and ovitrap as a means of controlling mosquitoes Aedes sp.The results showed that the larvitrap index in the larvitrap installation in Pandak Village was 60%, while in Mersi Village it was 56,7%. The ovitrap index in the ovitrap installation in Pandak Village was 36,7%, while in Mersi Village it was 33,3%. The number of larvae trapped in the larvitrap installation in Pandak Village were 832 larvae, while in Mersi Village there were 985 larvae. The number of eggs trapped in the ovitrap installation in Pandak Village were 518 eggs, while in Mersi Village there were 811 eggs.The conclusion of this research is that larvitrap is more effective to control Aedes sp than ovitrap. The community is advised to use larvitrap as a tool to control the Aedes sp (DHF vector.